Making Visible Leadership Characteristics and Actions in Fostering Collective Teacher Efficacy: A Cross-Case Study - Donald R. Mendenhall; Suzanne H. Jones; LeAnn G. Putney (Merits)
Poverty can contribute to students’ struggles with academic success, yet these struggles may be mitigated in schools with high levels of collective teacher efficacy (CTE). The purpose of this study was to identify effective Title I-eligible schools, serving a high percentage of financially disadvantaged students, while also maintaining high levels of CTE. Two schools were selected for cross-case analysis to explore how leadership characteristics and actions nurtured and sustained schoolwide CTE. The methodology used in this study was a qualitative cross-case analysis. The researchers purposefully selected the schools as cases based on the level of CTE existing in the schools. The qualitative cases provided means of determining how CTE was nurtured and sustained in the exemplary schools. These findings have substantial significance for educational leaders at the school, district, university and state levels. The results identified element characteristics and actions of instructional leaders to actuate CTE, increased teacher confidence and more significant collaborative relationships in schools. This study supports existing CTE research regarding connections between CTE and shared leadership, and CTE and trust among faculty.